Two-Fold Improved Poor Rich Optimization Algorithm based De-centralized Information Flow Control for Cloud Virtual Machines: An Algorithmic Analysis - Gurav, Yogesh B.; Patil, Bankat M. (2022 4th International Conference on Smart Systems and Inventive Technology (ICSSIT), 2022)
Today, cloud computing is being employed in many of organizations, owing to its higher computational efficiency, cost-effectiveness and flexibility. Nevertheless, security is being the major obstacle that hinders the success of the cloud computing platform. Therefore, the de-centralized Information Flow Control (DIFC) has been suggested as an appropriate solution for overcoming the security issues in the cloud. In the DIFC, the Conventional access control and encryption technologies weren'table to control the propagation of the tenant's private data efficiently in the system. Therefore, a novel DIFC framework with a hybrid AFS-ECC encryption model has been introduced. Within the hybrid AES-ECC encryption model, the optimal key selection has been carried out with the newly introduced Two-Fold Improved Poor Rich Optimization Algorithm (TF-IPRO). In this research work, an algorithmic evaluation has been carried out to validate the efficiency of the proposed TF-IPRO that has been utilized for optimal key selection during the de-centralized Information Flow Control for cloud Virtual Machines. The proposed TF-IPRO model has been validated by fixing the random value r as 0.2, 0.4, 0.6 and 0.8, respectively.